O off-line e a fantasia na comunicação instantânea via internet - Rodolfo, George Henrique Merino (2006)
The present work has the objective to make an analysis on the process of Instant Messaging through Internet, searching an intrinsic vision of the way, the internet users, the processes and its surroundings. An historical vision of the evolution of process of this tool to have a clear notion of its use and usefulness in differentiated occasions. Moreover, internet users were analyzed in a social-demographic vision in order to get a panorama of this new type of emissary/receptor of text, raising all the thematic one of the chats in details. On the other hand, it was argued the possibility of the existence of the fancy through the creation and experimentation of alternative identities, beyond considerations on the existence of virtual communities. It is conclude that the instantaneous communication by Internet is a difficult platform of virtual sociability, although not to hinder, the exercise of the fancy by means of the construction of alternative identities. Also it is verified that this model of communication disfavors the formation of virtual communities widely